The relationship between nitrate and phosphate nutrients in substrates with seagrass density: Implications for marine ecosystem sustainability - Rijal, Andi Afdalul (Institute for Advanced Science, Social, and Sustainable Future, 2025)
Introduction: Water conditions that greatly affect the density of seagrass species are the substrate fraction and nutrient content of the base substrate where the seagrass grows. This is important because seagrass utilizes dissolved nutrients in the waters and nutrients on the substrate for the production process. This study aims to determine the relationship between nitrate and phosphate nutrients on the substrate with seagrass density in Pajenekang Island, Liukang Tuppabiring District, Pangkep Regency, South Sulawesi. Methods: Data sampling of seagrass was carried out at north and west station using the line transect method where the data taken included seagrass frequency, cover, and density. Meanwhile, data collection of nitrate and phosphate nutrients on the substrate used a random sampling method and analysis with macro nutrien determination Morgan-Wolf extract. Findings: The results of study indicated that the seagrass density values in Pajenekang Island have various values, with the average seagrass density at the west station are 275 stands/m² and 356 stands/m² at the north station. The nutrient content on substrate in Pajenekang Island is low range when compared the result of other studies. Nitrate (0.36 ppm) and phosphate (0.49 ppm) at west station was significantly lower (P<0.05) compared to nitrate (0.49 ppm) and phosphate (0.64 ppm) at north station. The results of the Pearson correlation analysis among nitrate content and seagrass density on Pajenekang Island showed a negative relation with moderate correlation (-0.496*). Meanwhile, Pearson correlation analysis of phosphate content showed a negative relation by showing no relation (-0.166). This can be explained that there are other factors that effect on seagrass density in research location. Conclusion: It can be concluded that the seagrass density at Pajenekang Island varies. The average seagrass density at the western station is 275 individuals/m², while at the northern station, it is 356 individuals/m². Novelty/Originality of this article: The novelty of this research lies in analyzing the relationship between nitrate and phosphate nutrient content in the substrate and seagrass density on Pajenekang Island, which has not been widely studied in this region.